EL LLAMADO DIALECTO "SARÓNICO": REVISIÓN CRÍTICA - Pérez Molina, Miguel E. (Myrtia, 1986)
This article tries to do a revision of the dialectal group called "Saronic", formed by East Argolic, Corinthian and Megarian. The study of phonetic and morphological traits let us observe some differencies between West and East Argolic dialects. The contradicted testimonies found in the same phenomena show the lack of unity in East Argolic dialect. Besides, the fact that there are some discrepant features between East Argolic versus Corinthian and Megarian let us to think that tthe dialectal "Saronic" group, formed by these three dialects, sensu stricto does not exist.